English Features in Saudi Arabia: A Syntactic Study Within the World Englishes Framework - AlShurfa, Nuha; Alotaibi, Norah; Alrawi, Maather; Elyas, Tariq (Frontiers in Communication, 2022)
Saudi English has recently emerged as a new variety within the World Englishes framework. Many scholars have argued that there is still a gap in the literature and more studies on Saudi English are needed (Al-Rawi, 2012; Mahboob & Elyas, 2014). This study hopes to contribute to the growing research interest in Saudi English studies. The current study aims to identify Saudi English syntactic characteristics classified in relation to noun phrase, verb phrase, prepositional phrase, and clausal structure. Data were collected using three methods: conversation in natural settings, open-ended questions, and students’ writings. The findings confirm that substrate-superstrate interaction affects many syntactic characteristics of Saudi English.